Read2Me: A Cloud- based Reading Aid for the Visually Impaired - Thomas, RA; Ramanan, R; Roy, RA; Elisabath, S (International Journal of Computer Sciences and Engineering, 2025)
Reading is essential in our daily life. For the visually-impaired segment of the population, the inability to read has a substantive negative impact on their quality of life. Printed text (books, magazines, menus, labels, etc.) still represents a sizable portion of the information this group needs to have unrestricted access to. Hence, developing methods by which text can be retrieved and read out loud to the blind is critical. We use the computational power of resources made available by cloud computing providers for real-time image processing. There are many techniques which are used for navigating the visually challenged people, navigation in real time traffic is the main problem. The extracted text of various fonts and sizes then can be recognized individually and then combined in a word giving its output as audio using Text-to-speech using the SAPI libraries.